Ruptured hepatic artery aneurysms in the setting of polyarteritis nodosa: Buying time with endovascular embolization [Polyarterıtıs nodosa zemınınde rüptüre hepatık arter anevrızmalari: Endovasküler embolızasyon ıle zaman kazanmak] - (:unkn) unknown (Nobelmedicus, 2016)
Polyarteritis nodosa, a systemic necrotizing vasculitis of small and medium-sized arteries, can rarely present with isolated hepatic involvement and secondary, though at times fatal, spontaneously ruptured hepatic artery aneurysms. In this manuscript, systematic evaluation of a polyarteritis nodosa patient admitted to the emergency department due to severe abdominal pain and rapid deterioration of general condition is depicted. Patient’s -34-years-old, maleemergency abdominal computed tomography with contrast demonstrated hemorrhagic intrahepatic aneurysms and thus, selective coeliac catheter angiography was performed emergently. Massive active bleeding was verified and in order to stabilize the patient, aneurysms were embolized with urgent endovascular intervention, thereby achieving hemostasis to provide precious time for definitive medical treatment. Under similar circumstances, endovascular transcatheter interventions, when compared to surgical methods, are feasible and minimally invasive options for the diagnosis and evaluation of polyarteritis nodosa patients, treatment of complications and buying time for systemic medical treatment. © 2016, Nobelmedicus. All rights reserved.
Keywords: Aneurysm; Endovascular embolization; Hepatic artery; Polyarteritis nodosa; Rupture